In vitro and in vivo osteogenesis of rat adipose-derived stem cells combined with calcium alginate gel scaffold induced by calcitonin gene-related peptide - Huang, Changzhi; Liu, Xiaofeng; Lin, Liang; Zhang, Shimin; Xu, Nanyi; Wang, Xiaoyong; Lin, Jiuzao (Frontiers in Cell and Developmental Biology, 2025)
BackgroudBone defect repair is clinically challenging due to the limitations of traditional treatments. Tissue engineering holds great potential for constructing bone substitutes. This study evaluates the osteogenic capability of calcitonin gene-related peptide (CGRP)-induced rat adipose-derived stem cells (ADSCs) combined with calcium alginate (CaAlg) scaffolds both in vitro and in vivo.MethodsADSCs were isolated from rat inguinal fat pads, cultured, and characterized at passage 3. For in vitro experiments, cells were grouped and assessed over time using the CCK-8 assay for proliferation, alkaline phosphatase (ALP) activity assays, ALP staining, alizarin red staining (ARS), RT-PCR, and Western blotting for osteogenesis-related gene and protein expression. For in vivo experiments, constructs were evaluated after 12 weeks using X-ray, micro-CT, gross observation, and H&E staining.ResultsADSCs had clear surface antigen characteristics and displayed an “S”-shaped proliferation curve post-osteogenic induction. In vitro, CGRP and CaAlg scaffolds synergistically enhanced ADSC osteogenic differentiation, with higher early ALP activity and late-stage mineralization in the CGRP-ADSCs-CaAlg group. Additionally, osteogenesis-related gene and protein expressions were upregulated in CGRP-induced and scaffold-combined groups. In vivo, bone formation was observed in both ADSCs-CaAlg and CGRP-ADSCs-CaAlg groups, but not in the control group.ConclusionThese findings indicate that CGRP can induce ADSCs combined with CaAlg scaffolds to form tissue-engineered bone in vivo, with CGRP and CaAlg scaffolds showing a synergistic effect on promoting ADSC osteogenic differentiation.